Performance index as a monitoring aid towards sustainable urban transport / Muhammad Syazwan Baharum Nasir - Baharum Nasir, Muhammad Syazwan (2018)
Currently, Malaysia urban public transport service is facing difficulties in meeting user demands, traffic congestion is increasing as it hampers urban mobility and causes a major challenge to achieve as sustainable development.